Unveiling the food webs of tetrapods across Europe through the prism of the Eltonian niche. (30th December 2019) - O'Connor, Louise M. J.; Pollock, Laura J.; Braga, João; Ficetola, Gentile Francesco; Maiorano, Luigi; Martinez‐Almoyna, Camille; Montemaggiori, Alessandro; Ohlmann, Marc; Thuiller, Wilfried
Abstract: Aim: Despite recent calls for integrating interaction networks into the study of large‐scale biodiversity patterns, we still lack a basic understanding of the functional characteristics of large interaction networks and how they are structured across environments. Here, building on recent advances in network science around the Eltonian niche concept, we aim to characterize the trophic groups in a large food web, and understand how these trophic groups vary across space. Location: Europe and Anatolia. Taxon: Tetrapods (1, 136 species). Methods: We combined an expert‐based metaweb of all European tetrapods with their spatial distributions and biological traits. To understand the functional structure of the metaweb, we first used a stochastic block model to group species with similar Eltonian niches, and then analysed these groups with species' functional traits and network metrics. We then combined these groups with species distributions to understand how trophic diversity varies across space, in function of the environment, and between the European ecoregions. Results: We summarized the 1, 136 interacting species within the metaweb into 46 meaningful trophic groups of species with a similar role in the metaweb. Specific aspects of the ecology of species, such as their activity time, nesting habitat and diet explained these trophic groups. Across space, trophic diversity was driven by both biotic and abiotic factors (species richness, climate and primary productivity), and the representation of trophic groups differed among European ecoregions. Main conclusions: We have characterized the Eltonian niche of species in a large food web, both in terms of species interactions and functional traits, and then used this to understand the spatial variation of food webs at a functional level, thus bringing together network science, functional ecology and biogeography. Our results highlight the need to integrate multiple aspects of species ecology in global change research. Further, our approach is strongly relevant for conservation biology as it could help predict the impact of species translocations on trophic diversity.